Flourishing as international students and scholars in the US - Cao,XE; Liu,X; Zhang,Y (Matter, 2022)
International students and scholars in the US face many internal and external challenges: barriers in writing, presentations, and interviews, difficulties in building professional networks, visa and funding restrictions, and ineligibility for many fellowship opportunities. Here, three international students and scholars use first-person narratives to share their unique experiences tackling these challenges. They also suggest what institutions can do to support the international student and scholar community.